Legal Protection Provided by the Women and Children Protection Unit of the Gorontalo Regional Police for Victims of Online Prostitution Crimes - Nurmala, Leni; Dince Aisa Kodai; Rahmad Paneo (Al-Mahkamah: Jurnal Hukum, Politik dan Pemerintahan, 2024)
The aim of this research is to examine the forms of legal protection for child victims of online prostitution crimes and efforts to deal with children as victims of online prostitution crimes. The approach used is an empirical normative juridical method by collecting data through documentation and direct interviews with investigators in the women and children unit at the Gorontalo Regional Police, especially those who handle child victims of online prostitution crimes. A social phenomenon that has recently occurred in social life is the problems that occur with children. The existence of children who are positioned as individuals who are still very vulnerable and weak and therefore have the potential to become victims of criminal acts. As happened in Gorontalo in 2023, the Gorontalo Regional Police Team found 5 children who were victims of criminal acts of human trafficking by using children as online prostitution workers offered by the perpetrators via electronic short messages (whatsapp, michat). Children who are victims of criminal acts of prostitution must receive special protection based on Law Number 35 of 2014. The Women and Children Protection Unit of the Gorontalo Regional Police provides special protection based on Article 59 to child victims of criminal acts of online prostitution. All actions that include services and assistance to victims. The legal efforts taken are preventive and repressive. Preventive efforts include conducting outreach to the public regarding the modus operandi of criminal acts of human trafficking which result in turning victims into prostitution, repressive efforts include implementing heavy criminal sanctions for the perpetrators.